All but B, as on B an a can be factored out
Answer:
x= -3
Step-by-step explanation:
x equals to -3 is the standard form
Answer:
Solution of the equation 4x + 5 = 3x + 4 is:
x= -1
Step-by-step explanation:
We are given a equation:
4x + 5 = 3x + 4
We have to solve the equation for x
4x+5=3x+4
subtracting both sides by 4
4x+5-4=3x+4-4
4x+1=3x
subtracting both sides by 4x
4x|+1-4x=3x-4x
1= -x
⇒ x= -1
Hence, solution of the equation 4x + 5 = 3x + 4 is:
x= -1
Answer:
-7/3
Step-by-step explanation:
2(6−4)=3(6+2)
2(6x-4)=3(6x+2)
Solve
1
Distribute
2(6−4)=3(6+2)
{\color{#c92786}{2(6x-4)}}=3(6x+2)
12−8=3(6+2)
{\color{#c92786}{12x-8}}=3(6x+2)
2
Distribute
12−8=3(6+2)
12x-8={\color{#c92786}{3(6x+2)}}
12−8=18+6
12x-8={\color{#c92786}{18x+6}}
3
Add
8
8
to both sides of the equation
12−8=18+6
12x-8=18x+6
12−8+8=18+6+8
12x-8+{\color{#c92786}{8}}=18x+6+{\color{#c92786}{8}}
5 more steps
Solution
=−7/3